The University Library as Centre for Research on the History of the University - F. Dárdai, Ágnes (Per Aspera ad Astra, 2014)
Since its foundation in 1923, the Library of the University of Pécs has been one of the research centres for the historical study of the University of Pécs. Its core collection, the former episcopal library (Klimo Library), was originally created to serve as a university library. Its holdings, which continued to grow until the beginning of the 20th century, were offered to the Royal Erzsébet University after its removal from Pozsony (today Bratislava) to Pécs. The management of the library, while acknowledging the work of its predecessors, fostered knowledge related to Klimo Library at the turn of the millenium by employing specialists, whose task it has been to perform research on the library holdings and to organize conferences. Since 2006, the library has had the task of the curatorship of the historical collections of the university. The Department of Historical Collections, founded in the Spring of 2006, warranted the integration of the originally distant collections, its tasks being the arrangement of the historical sources, making the library holdings available to researchers, organizing conferences and exhibitions, editing volumes of publications and editing the periodical for the history of the University. Our colleagues take an active part in research, especially in the fields of history in general and local history, the history of higher education, and cultural history. (Translated by Gabriella Hartvig) Photo: Historical Collection Department of the Central Library